2019
DOI: 10.2151/sola.2019-022
|View full text |Cite
|
Sign up to set email alerts
|

Convective Structure Changes over the Equatorial Pacific with Highly Increased Precipitation under Global Warming Simulated in the HiRAM

Abstract: While most studies have argued a slower increase of 1−3% K −1 of precipitation globally, others note that this is not necessarily the case from a regional perspective. In this study, we examine the convective structure changes over the equatorial Pacific with highly increased precipitation under global warming using simulations from the High Resolution Atmospheric Model (HiRAM). The moisture budget analysis shows that the precipitation increases must result from a significant enhancement of convection, with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…For the two future projection experiments, the SST and SIC data were obtained from ensemble means of Coupled Model Intercomparison Project Phase 5 (CMIP5) models with the RCP8.5 emission scenario. We select the RCP8.5 scenario because it has been widely used to project the potential changes of severe weather events like tropical cyclone (Tsou et al ., 2016; Chen et al ., 2020) and heavy rainfall (Bui and Maloney, 2018; Liu et al ., 2018; Bui et al ., 2019) under global warming. According to a recent report of Schwalm et al .…”
Section: Data Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the two future projection experiments, the SST and SIC data were obtained from ensemble means of Coupled Model Intercomparison Project Phase 5 (CMIP5) models with the RCP8.5 emission scenario. We select the RCP8.5 scenario because it has been widely used to project the potential changes of severe weather events like tropical cyclone (Tsou et al ., 2016; Chen et al ., 2020) and heavy rainfall (Bui and Maloney, 2018; Liu et al ., 2018; Bui et al ., 2019) under global warming. According to a recent report of Schwalm et al .…”
Section: Data Model and Methodsmentioning
confidence: 99%
“…For the two future projection experiments, the SST and SIC data were obtained from ensemble means of Coupled Model Intercomparison Project Phase 5 (CMIP5) models with the RCP8.5 emission scenario. We select the RCP8.5 scenario because it has been widely used to project the potential changes of severe weather events like tropical cyclone (Tsou et al, 2016;Chen et al, 2020) and heavy rainfall (Bui and Maloney, 2018;Liu et al, 2018;Bui et al, 2019) under global warming. According to a recent report of Schwalm et al (2020), RCP8.5, the most aggressive scenario, is not only in close agreement with historical total cumulative CO 2 emissions (within 1%) but also the best match out to midcentury under current climate policies with highly plausible levels of CO 2 emission to the end of the 21st century.…”
Section: Model and Experiments Designmentioning
confidence: 99%
“…Designed for global cloud‐resolving capability, HiRAM uses a nonintrusive shallow convective scheme (Bretherton et al ., 2004) and replaces the deep convective scheme by a six‐category bulk cloud microphysics scheme for the resolved component of cumulus convection processes (Zhao et al ., 2009). As a new member contributed to the upcoming CMIP6 (Coupled Model Intercomparison Project, phase 6), HiRAM has been used to study TC seasonal forecast over the North Atlantic (Zhao et al ., 2010; Chen and Lin, 2011) and eastern Pacific (Jiang et al ., 2012), as well as to project changes of TC activity over the western North Pacific (Tsou et al ., 2016) and changes of convection activity across the tropical Pacific under global warming (Bui et al ., 2019).…”
Section: Data Model and Methodsmentioning
confidence: 99%
“…The physical mechanisms of natural systems were investigated using different approaches in an attempt to achieve a more accurate climate projection. Precipitation is one of the critical parameters that climate change will influence and that will induce risk, hence the following were studied in great detail in Taiwan: the land-sea breeze system that that facilitates the formation of diurnal rainfall events [34][35][36], and seasonal monsoon events, including Madden-Julian oscillation impacts on winter rainfalls, and the East Asian summer monsoon (aka Meiyu), under different climate scenarios [37,38]. The preliminary study of watershed typhoon rainfalls and extreme precipitation under climate change found that the 24-h duration precipitation depth for 20-year and 100-year extreme events are likely to increase, suggesting concerns about the current hydrologic designs of critical infrastructures [39][40][41][42].…”
Section: Adaptation Research Policy Support and Advocacymentioning
confidence: 99%